Alternative methods of conflict resolution and intercultural mediation: strategies for multicultural contexts - Raul Alejandro Viviescas-Cabrera; Jéssica Marisol Vera-Carrera (Eleuthera, 2025)
This work explores the evolution and application of Alternative Conflict Resolution Methods (ACR) with a special focus on intercultural mediation in Colombia. Through a qualitative design and documentary analysis, the key phases of intercultural mediation are reviewed, from its beginnings in the 1990s, its expansion in the educational field at the beginning of the 21st century, to its recent reconfiguration as a comprehensive strategy to promote coexistence and social peace. Specific studies by Giménez (1997), Cuadros Riobó (2001), Valero Garcés and Guzmán Mancho (2002), Llevot (2002), and Ortiz-Cobo (2006) are highlighted, illustrating how intercultural mediation has been adapted in different contexts. The analysis emphasizes the need for comprehensive training of mediators, a preventive and educational approach, structural interventions, and a dialogic and deconstructive approach. The conclusions emphasize the importance of continuing the academic and practical development of intercultural mediation as an essential tool for managing multicultural conflicts and building lasting peace in diverse territories such as Colombia.